The Caloocan City Public Library an evaluation with implications for collection development - Dizon, Marie C.; Pascua-Cruz, Ma. Divina A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1997)
The study was conducted to: 1) to ascertain the users' perceptions on the collection of the Caloocan City Public Library; 2) to determine the strengths and weaknesses of the collection; 3) to find out whether Caloocan City Public Library's staffing, physical facilities and collection meet the Minimum Standards for Public Libraries; and 4) to find out the programs of the library in upgrading the collection to meet the minimum requirements of the Standards for Public Libraries.
The major findings of the study are: 1) majority of the respondents are students; 2) the Caloocan City Public Library users do not visit the library regularly; 3) the library materials that are most frequently used are books and reference books; 4) the Caloocan City Public Library is short of professional staff but overstaffed of seven non-professionals as per Minimum Standards; and 5) the library has a total book collection of 6,708 volumes, way below the standard 10,000 volumes for a city public library; and 6) the library meet the standards with regards to its physical facilities. Based on these findings, the following conclusions were drawn: 1) The general public have not recognized the Caloocan City Public Library as an institution that could provide their information, recreation and research needs. This is borne out by the fact that clients of the library consist mostly of students rather than the general public. The Caloocan City Public Library failed to lure the general public to use its collection and services. 2) The Caloocan City Public Library's collections and services, as seen by its clients, are adequate. However, as per Minimum Standards for Public Libraries, its collections, particularly the book collection, are sub-standard and are not equally developed in the different subject fields. Its physical facilities, though, are within the minimum standards. 3) The Caloocan City Public Library's program of collection development seems very weak. It has been hampered by lack of funds.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: Caloocan City Public Library; Public libraries -- Evaluation. -- Philippines -- Caloocan City